Prevalence, impact and cultural context of psychotic experiences among ethnic minority youth. Issue 3 (7th August 2014) - Adriaanse, M.; van Domburgh, L.; Hoek, H. W.; Susser, E.; Doreleijers, T. A. H.; Veling, W.
Abstract : Background: The risk for psychotic disorders is increased for many ethnic minority groups and may develop in early childhood. This study investigated whether the prevalence of psychotic experiences (PE) with high impact is higher among ethnic minority youth compared to majority youth and examined the significance of these PE. Method: A school-based study assessed a large community sample of 1545 ethnic minority and majority children in The Netherlands (mean age 12.98 ± 1.81 years). The Dutch ( n = 702, 45.4%), Moroccan-Dutch ( n = 400, 25.9%) and Turkish-Dutch ( n = 170, 11.0%) ethnic groups could be studied separately. Self-report questionnaires on PE, impact and cultural context were administered. Results: Prevalence of PE with high impact was 3.1% in Dutch, 9.5% in Moroccan-Dutch and 7.1% in Turkish-Dutch youth. Compared to Dutch youth, odds ratios were 3.0 [95% confidence interval (CI) 1.7–5.1] for Moroccan-Dutch youth and 2.2 (95% CI 1.1–4.6) for Turkish-Dutch youth. Differences were not explained by cultural or religious differences. Conclusions: The increased risk for psychotic disorders in ethnic minorities may already be detectable in childhood, since PE with high impact were more common among ethnic minority youth compared to majority youth. The additional measurement of impact of PE appears to be a valid approach to identify those children at risk to develop psychotic or other more common psychiatric disorders.